LIABILITY OF TEMPORARY LAND DEED OFFICIALS FOR NEGLIGENCE IN READING DEEDS DURING SALE AND PURCHASE TRANSACTIONS - Ajie, Dimas Ghifari; Yunithawati R , Yenni; Laela F, Efa (Faculty of Law, Universitas Lampung, 2024)
Land Deed Officials (PPATs) play a crucial role in ensuring the legal certainty of the authentic deeds they prepare. Temporary PPATs share the same primary duties and authorities as regular PPATs and are required to comply with relevant regulations. The issue arises when a Temporary PPAT fails to read the authentic deed in front of the parties, leading to questions about responsibility and legal consequences. This research examines these concerns in light of Government Regulation Number 24 of 2016, which amends Government Regulation Number 37 of 1998 concerning the Position of Land Deed Officials. Employing a normative juridical research method, the research analyzes secondary data from legal materials, complemented by primary data gathered through interviews. The research is descriptive-analytical, using qualitative juridical data analysis. The findings reveal that a Temporary PPAT’s failure to read the authentic deed before the parties, as required by Article 22 of the Government Regulation on the Position of PPAT, results in the deed being classified as an underhand deed or null and void. This negligence has legal ramifications, including administrative, civil, and criminal liability. The Temporary PPAT can be held accountable if it is proven that their failure caused harm to the parties, leading to potential sanctions if the Temporary PPAT’s unlawful actions are substantiated.